Cardiovascular medication: improving adherence using prompting mechanisms - Glynn, Liam (BMJ Clin Evid, 2015)
INTRODUCTION: Adherence to medication is generally defined as the extent to which people take medications as prescribed by their healthcare providers. It can be assessed in many ways (e.g., by self-reporting, pill counting, direct observation, electronic monitoring, or by pharmacy records). This overview reports effects of prompting mechanisms on adherence to cardiovascular medications, however adherence has been measured. METHODS AND OUTCOMES: We conducted a systematic overview, aiming to answer the following clinical question: What are the effects of prompting mechanisms to improve adherence to long-term medication for cardiovascular disease in adults? We searched Medline, Embase, The Cochrane Library, and other important databases up to May 2014 (BMJ Clinical Evidence reviews are updated periodically; please check our website for the most up-to-date version of this review). RESULTS: At this update, searching of electronic databases retrieved 174 studies. After deduplication and removal of conference abstracts, 80 records were screened for inclusion in the overview. Appraisal of titles and abstracts led to the exclusion of 45 studies and the further review of 35 full publications. Of the 35 full articles evaluated, one RCT was added at this update. We performed a GRADE evaluation of seven PICO combinations. CONCLUSIONS: In this systematic overview, we categorised the efficacy for seven comparisons based on information relating to the effectiveness and safety of prompting mechanisms, alone and in combination with reminder packaging or patient education.